ANALISIS TRANSPARANSI DAN AKUNTABILITAS DALAM PENGELOLAAN DANA DESA (STUDI KASUS PADA DESA LIMBANGAN DI BREBES) - Firmansyah, Fahmi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Accountability is a form of accountability carried out by the government to report and present activities that have been carried out to the public. This accountability can be used as a basis for implementing transparency in every activity implementation. This research aims to determine and assess accountability and transparency in the management of village funds carried out by the Brebes Village Government, Brebes Regency. This research uses descriptive qualitative methods with the Nvivo 12 Plus tool. The data collection technique used was interviews. This interview was conducted involving the village government, totaling 3 informants. The results of this research indicate that the financial management of village funds by the Limbangan Village Government is in accordance with applicable laws. the transparency process carried out by the village government, namely using information media in the form of a banner detailing funds placed at the village office. Even though the management of village funds that has been carried out by the village government is quite good, it still needs to be improved, and there must be outreach to the community to participate in the implementation and utilization of village funds